2016
DOI: 10.7160/aol.2016.080209
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Broadband for the Farmers: A Case Study of Technology Adoption by Cocoa Farmers in Southern East Java, Indonesia

Abstract: The objective of this paper is to examine the factors that affect Indonesia cocoa farmer intention to use mobile phone application. The main factors examined in this study are perceived usefulness (PU), perceived ease of use (PEOU), business factors and individual factors. The study sample consists of 191 respondents in thirteen cocoa farmer centers in southern East Java. Data were analyzed by employing Structural Equation Modeling (SEM). The findings revealed that the user intention on adopting mobile phone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Previous research has evidence on the effect of socio-economic characteristics on technology adoption (Nabhani et al, 2016). Our study tests the effect of some socio-economic characteristics on perceived usefulness and perceived ease of use of mobile phones.…”
Section: Socio-economic Characteristicsmentioning
confidence: 96%
“…Previous research has evidence on the effect of socio-economic characteristics on technology adoption (Nabhani et al, 2016). Our study tests the effect of some socio-economic characteristics on perceived usefulness and perceived ease of use of mobile phones.…”
Section: Socio-economic Characteristicsmentioning
confidence: 96%
“…Djokoto et al (2016) also found that being male, having small household size, having young cocoa trees, access to extension services and access to credit positively influenced the adoption of organic cocoa technology. A study by Nabhani et al (2016) also found competitiveness pressure and perception of cost as factors that determine adoption of technologies by cocoa farmers. Furthermore, Ali et al (2018) found farmers engagement in off-farm economic activities, extension contacts, farm size, hired and family labour and the value of productive farm assets to be the factors that determine adoption of fertilizer among smallholder cocoa farmers.…”
Section: Literature Reviewmentioning
confidence: 97%
“…The eNAM is simple in operation and learnt without difficulty (Auramo et al, 2005), (Engotoit et al, 2016), (Michels et al, 2019) 3 Social Influence Close friends, leading farmers, associated traders, and community leaders encourage or promote the eNAM (Ajzen, 1991), (Venkatesh et al, 2003(Venkatesh et al, , 2012, (Dejen & Solomon, 2015), (Engotoit et al, 2016), (Dwivedi et al, 2019) 4 Trust The user's confidence in the information and trade based on e-trading. It also signifies a belief that the eNAM is reliable and that the management will act in the interest of farmers and other stakeholders (Moorman et al, 1992), (Killpatrick & Factor, 2000), (Ridings et al, 2002), (Kuttainen, 2005), (Casalo et al, 2011), (Ramesh et al, 2012), (Bisen & Kumar, 2018), (Jayashanker et al, 2018), (Wiyada et al, 2018) 5 Cost The transaction costs in the eNAM platform (Dodd et al, 1991), (Garicano & Kaplan, 2001), (Clasen & Mueller, 2006), (Solaymani et al, 2012), (Seifbarghy & Esfandiari, 2013), (Dey, 2016), (Nabhani, 2016), (Mustaqquim, 2017), (Wiyada et al, 2018) 6 Facilitating Conditions…”
Section: Variable Explanation In Study Context References 1 Perceived Usefulnessmentioning
confidence: 99%